PENGARUH DIMENSI PELAYANAN DALAM PEMBUATAN E-KTP TERHADAP KEPUASAN MASYARAKAT PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BENGKULU - Selvi Juwita; Ade Hirawan; Onsardi Onsardi (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
The purpose of the study was to determine the effect of tangible, tangible, responsiveness, assurance and empathy on people's satisfaction at the Department of Population and Civil Registration of Bengkulu City. This type of research is quantitative research, the method of data collection is done by using observation, documentation and questionnaires. The sample in this study was 145 people who took care of e-KTP at the Department of Population and Civil Registration of Bengkulu City. Analysis of the data used is multiple linear regression test, test of determination and hypothesis testing. Tangible does not have a significant effect on community satisfaction, tangible has not been able to increase community satisfaction. Reliability has a positive and significant effect on community satisfaction, because the services provided by employees are able to increase community satisfaction. Responsiveness has a positive and significant effect on community satisfaction, this illustrates that the reliability of employees in providing services is able to increase community satisfaction. Assurance has a positive and significant effect on community satisfaction, if Assurance increases, community satisfaction will increase. Empathy has a positive and significant influence on community satisfaction because the empathy given by employees is able to increase community satisfaction. Keywords: Service Dimensions, E-KTP, Community Satisfaction